2017
DOI: 10.1039/c6cp06940a
|View full text |Cite
|
Sign up to set email alerts
|

The initial stages of melting of graphene between 4000 K and 6000 K

Abstract: Graphene and its analogues have some of the highest predicted melting points of any materials. Previous work estimated the melting temperature for freestanding graphene to be a remarkable 4510 K. However, this work relied on theoretical methods that do not accurately account for the role of bond breaking or complex bonding configurations in the melting process. Furthermore, experiments to verify these high melting points have been challenging. Practical applications of graphene and carbon nanotubes at high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 25 publications
(33 reference statements)
5
63
0
Order By: Relevance
“…It is indeed known that laser-induced heating can cause AuNPs to melt (1063 ℃ melting point) and/or fragment 18 , 19 . The exact reason why this phenomenon does not occur for GQDs is not known, but it may be linked to their much higher melting temperature of ~4000–6000 ℃ 20 . In comparison, TEM images showed that the size of the GQDs is more gradually reduced upon subsequent laser pulses (Figure S4 ), most likely due to removal of CO 2 /CO 2 H groups.…”
Section: Resultsmentioning
confidence: 99%
“…It is indeed known that laser-induced heating can cause AuNPs to melt (1063 ℃ melting point) and/or fragment 18 , 19 . The exact reason why this phenomenon does not occur for GQDs is not known, but it may be linked to their much higher melting temperature of ~4000–6000 ℃ 20 . In comparison, TEM images showed that the size of the GQDs is more gradually reduced upon subsequent laser pulses (Figure S4 ), most likely due to removal of CO 2 /CO 2 H groups.…”
Section: Resultsmentioning
confidence: 99%
“…It is significant, however, that the very form of Hamiltonian (11) indicates the crucial role of multiphonon processes in the occurrence of conditions for the transition of graphene into a phase with abnormally large fluctuations of the bending component of the strain tensor. Since the formation of defects (in the case of graphene, this may be the already mentioned Stone-Wales defects [9,10]) is due to precisely multi-phonon processes, the theory proposed in this paper is naturally linked with ideas about the melting of a crystal as the result of its "softening" due to the thermal creation of defects [3,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Really, besides the value W S− E ≈ 4.6 eV [9,10] indicated in the Introduction, in the literature one can find calculated values from 4.8 eV and 5.2 eV [37] to 5.8 eV [38] and even 6.0 eV [39]. It should be borne in mind that the estimation of ∞ T should rather be associated not with W S− E , but with the height of the barrier, which separates the ground state of graphene and the state in the presence of the Stone-Wales defect.…”
Section: Self-consistent Calculation Of the Graphene Melting Critmentioning
confidence: 99%
“…AlB 6 , Cu 2 Si) [12][13][14][15][16][17] have enriched the "family" of 2D nanomaterials. 18,19 These layered nanomaterials exhibit many unique properties compared with zero-dimensional (0D) nanoparticles, one-dimensional (1D) nanowires, three-dimensional (3D) networks, and their bulk counterparts, 18,[20][21][22] which have attracted considerable efforts for exploration of other 2D nanomaterials. Recently, 2D metal-organic framework (MOF) nanosheets, a new class of crystalline porous materials constructed by linking metal nodes (e.g., metal ions, clusters) with organic ligands (e.g., carboxylate ligands, other negatively charged ligands), 23 have attracted increasing research interest.…”
Section: Introductionmentioning
confidence: 99%